Effects of age and task difficulty on neuromuscular and corticomuscular determinants of walking balance - Costa, Andréia Abud da Silva (2024)
Walking balance is critical determinant of human mobility and functional independence. Walking balance is the ability to keep the center of mass within the base of support while walking, and relies on an intricate coordination between sensory and muscular function. Healthy aging is a progressive degenerative process that impairs, among others, walking balance. This impairment manifests itself in the reduced ability to adapt to internal and external perturbations while walking. However, the effects of natural aging on walking balance can go unnoticed when walking task difficulty is low. In this context, beam walking is emerging as a novel paradigm for assessing walking balance. This is because walking on a narrow beam makes it difficult to keep one\'s balance. The cause of this increase in difficulty is related to a reduction in the base of support which in turn requires greater foot-placement precision. With a reduction in the base of support, the chances of the center of mass moving outside of the base of support while it pivots over the stance leg during gait are increased, possibly causing a \"fall\", i.e., step-off the beam. Therefore, this thesis aimed to examine the effects of age and walking task difficulty on walking balance, assessed by beam walking. Walking task difficulty was altered in two ways: 1. Changing the walking surface and 2. Manipulating mechanical, cognitive, and postural constraints of beam walking. The effects of age were assessed cross-sectionally comparing age groups. In general, it was expected that age and increased task difficulty would affect walking balance measured by beam walking. It was also hypothesized that decreases in walking balance would be accompanied by changes in neuromuscular and neural control. Therefore, we compared the distance walked on beams of 6-, 8-, and 10-cm-wide, with and without a cognitive dual-task, and with the arms free, crossed in front of the chest, or akimbo (Chapter 2). It was observed that the 6-cm-wide (vs. 8- and 10-cm-wide) beam and crossed arms (vs. akimbo and free) were the constraints that imposed greater difficulty on older adults\' walking balance. The insertion of the cognitive task reduced step speed but did not affect the walking balance. Based on the outcomes, we standardized the use of the 6-cm wide beam in the subsequent studies. In Chapter 3, we examined the effects of age and walking task difficulty on the neuromuscular control of walking balance using kinematics and muscle synergy analyses. In this study, we manipulated walking task difficulty by changing walking surface (tape overground vs. 6-cm wide beam). To address these effects on neuromuscular control, we estimated the complexity, coactivity, and efficiency of muscle synergies. In addition, walking balance and margin of stability were also assessed. We observed that older adults reduced the complexity and efficiency of neuromuscular control to maintain the walking balance comparable to young adults. In Chapter 4, we aimed to determine the effects of age, cognitive task, and arm position on neuromuscular control of walking balance. Again, we compared walking balance, margin of stability, and muscle synergy metrics between older and young adults. However, in this study, participants walked only on the 6-cm-wide beam, still alternating trials with and without cognitive task, and with free and crossed arms. The factors affected walking balance neuromuscular control in differently. Age reduced muscle synergy complexity and efficiency, while cognitive task increased muscle synergy coactivity and decreased its efficiency, and crossing arms only reduced muscle synergy complexity. For a deeper understanding of the neural control of walking balance, the experiment in Chapter 5 examined the effects of age and walking balance difficulty on beta-band (13-30 Hz) corticomuscular and intermuscular coherence while manipulating walking surface (overground, a ribbon affixed to the floor, 6-cm wide beam). We observed that walking balance difficulty increased corticomuscular and intermuscular coherences, while age enhanced corticomuscular but not intermuscular coherence. All the changes were seen more frequently during swing phase. Chapter 6 summarizes and discusses the main findings of this thesis. The results were discussed with a perspective on beam walking as an emerging paradigm to assess walking balance during natural aging and on selected potential neural mechanisms underlying the observed age- and difficulty-effects on walking balance during beam walking. Age-related declines in walking balance are more evident in more difficult walking tasks, maybe due to a worse cognitive resource-sharing caused by a less automated gait in older adults. Therefore, even with neural and neuromuscular adaptations, in an attempt to maintain walking balance performance in difficult walking tasks, older compared with younger adults still walk shorter distances.